Optimizing schedule of boarding school using vertex and edge coloring approach / Nurhuda Ismail, Siti Sarah Raseli and Nur Farhana Mohd Asri - Ismail, Nurhuda; Raseli, Siti Sarah; Mohd Asri, Nur Farhana (Universiti Teknologi MARA, Perak, 2021)
Soft skills like time management, teamwork and effective communication are highly important nowadays. But, many students are still lack of knowledge regarding all these skills. It is because, students are too much concerned with academic excellence until they neglect the mastery of the skills that they should have. This study focused on one of the boarding schools in Malaysia located in Kedah known as Sekolah Menengah Sultan Abdul Halim (SMSAH). The aim was to increase the awareness of the importance of soft skills within themselves. The important of this study in order to achieve this goal is to optimize the school schedule using the Graph Coloring method. In this study, two approaches have been used under the Graph Coloring method which are Vertex and Edge Coloring. Greedy Algorithm has been used to solve the Vertex Coloring approach while Graph Coloring Algorithm has been used to solve the Edge Coloring approach. The algorithm that produced the lowest minimum color will be selected for implementing the schedule of the boarding school. The result has shown that the Greedy Algorithm has succeeded to produce the very minimal color for the boarding school scheduling.